Warmians in the 19th century – reflection on identity and the cultural border - Lewandowska, Izabela (Marginesy, 2021)
The article presents the problems of the identity of the Warmians living on the cultural border in the 19th century. Warmians as an ethnic group have lived in the historical region of Warmia since the Middle Ages. In the modern period (16th–18th c.), Warmia belonged to the Polish state, was ruled by Polish bishops, there was a large influx of Polish settlers, there developed the Polish culture, and the dialect was mainly based on Polish vocabulary. The situation changed after 1772, when Warmia was occupied by the Prussian state. Throughout the 19th century the Germanization processes took place in this area, manifesting mainly in the elimination of the Polish language and the formation of the German national identity. The Warmians lived on a cultural border, as both nations had great influence over the region. They chose locality, which manifested in devotion to the Catholic church, traditional customs, and the Warmian dialect. That is why they have kept their individuality and identity until today.